Estudio de mercado para determinar la implementación de sucursal de distribución para la empresa MUNDOFFICE C. LTDA, en la cuidad se Santo Domingo de los Tsáchilas periodo 2010-2011 - Gómez Freire, Juli Mercedes (2011)
The Market Study to determine the implementation of a distribution branch for the company Mundoffice C.Ltda, in the city of Santo Domingo de los Tsáchilas, period 2010-2011. The main objective of the research was to know in detail the market of office supplies and school supplies, in the urban area of ​​the Santo Domingo de los Tsáchilas canton, with the purpose of determining the implementation of a distribution branch for the company Mundoffice C.Ltda . In Chapter I, the conceptual framework of the research is presented. The problematization, formulation of the problem, delimitation among others. To finalize it, the variables of the hypothesis and the operationalization of the variables are presented. In Chapter II develops the theoretical framework the fundamentals of the research are raised, among which include market segmentation, market, measurement of the level of satisfaction. Chapter III contains research methodology. It records location, types of location, methods, which were used in market research, including types of research, sources of information, calculation of sample size and distribution of sample sources, surveys, and processing of the information summarized in tables and graphs, each one with its respective analysis and interpretations. They highlight, on the one hand, the information obtained from the institutions (consumers of office supplies) and, on the other hand, that of the students (consumers of school supplies) of Santo Domingo de los Tsáchilas, the main conclusions of the research are presented of market: AIDIPA and DILIPA are the strongest companies that market office supplies followed by LNS and SUPER PACO; the most important aspects considered by entrepreneurs and consumers when making purchases are the location of the point of sale, the price and the guarantee of the products; The office; most buyers of office supplies and school supplies have not benefited from promotions; there is an unmet demand for office supplies, computers and school supplies in the city of Santo Domingo de los Tsáchilas. The main recommendations are included: develop market strategies that allow competing with AIDIPA and DILIPA, the strongest companies that market office supplies; use as a tactic of introduction prices of "denate" (lower than those of the market); Locate the point of sale of the company MUNDOFFICE C.LTDA., In the center of the city of Santo Domingo de los Tsáchilas; design a promotions plan that benefits buyers of office supplies and school supplies; meet the unmet demand for office materials, computers and school supplies in the city of Santo Domingo de los Tsáchilas, by designing a proposal that formulates the alternative for the implementation of a distribution branch for the company MUNDOFFICE C.TLDA. in that city. Chapter IV describes the analysis and interpretation of the results. Chapter V includes the conclusions, recommendations of the results of the investigation. In Chapter VI, the appropriate project proposal is developed. The proposal is presented to determine the implementation of a distribution branch for the company MUNDOFFICE C.LTDA in the city of Santo Domingo de los Tsáchilas period 2010-2011. This chapter includes the justification, the objectives and the analysis of the human, material and financial feasibility of the same. It included the Forecast of sales and expected increase of income and profits of the Mundoffice distribution branch, the economic balance of cash flow, the calculations of the T.I.R and the V.A.N, the capital recovery. The summary of the economic indicators of this investment project shows the following: Internal Return Rate IRR = 41.70%> discount rate 15%. ACCEPTED; Net Present Value VAN = $$ 85,331.15> initial investment ($ 149,500.00). ACCEPTED; Investment recovery time = 3 years <useful life of the project (5 years). ACCEPTED; In conclusion, the financial criteria